The Implementation of Culture-Based Extracurricular Activities at SMP N 2 Pajangan - Anggie Nadia Dinihari (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
Karawitan and traditional dance are two of culture-based extracurricular acrivities. This study aims to evaluate both of extracurricular activities in order to find information to be used in judging alternatives. This is a kind of evaluative study. The data were gained from interview, documentation, and also observation. School administrator, students, and instructor became the participants of this study. Analysis data of this study used descriptive qualitative analysis which focused on each aspect based on the CIPP model evaluation. Data were presented narratively by adding quotation from the interview. The study found that from the context evaluation, school administrators were right in choosing karawitan and traditional dance as the culture-based extracurricular activities. This met the needs of environment. However, for traditional dance should have instructor. From the input process, schools administrators selected students which wanted to follow the extracurricular activities then choose some of them. This was aimed to have balance quota for each extracurricular activities. For the process evaluation, authors found that the room can affect to the process of activities. Room should be bigger so that the process of extracurricular runs well. For the last is product evaluation. Product for traditional dance is better for individual only. That is why school administrator is hoped to make better improvement for both extracurricular activities.